EFISIENSI DAN EFEKTIFITAS SERTA KINETIKA ELEKTROKOAGULASI PENGOLAHAN LIMBAH SAGU AREN - Sutanto, -; Iryani, Ani; Sarahwati, - (Fakultas Matematika dan ilmu pengetahuan Alam. Universitas Pakuan.)
The processing of palm sago into flour produces unsightly brownish wastewater with high COD and TSS values and very low DO. Waste treatment to reduce waste parameter values can be done one of them by electrocoagulation method. This study was conducted to determine the effectiveness of processing sago wastewater by electrocoagulation and decreasing kinetics of TSS and COD. Electrocoagulation batch system was carried out using 5 x 10 cm aluminum electrode, 3 cm electrode distance. Application of voltage variations: 15; 18; and 20 volts with electrocoagulation time variation 15; 30; and 60 minutes. The results showed that the best electrocoagulation at 18 volts and 60 minutes time, namely the efficiency of reducing TSS and COD values respectively 89.17% and 58.28%, and can increase the DO value from 2.5 to 6.8 mg / L The kinetics of decreasing TSS and COD follow the one order with a constant decrease of respectively - 0.012 and -0.013 per minute.Key words: Electrocoagulation, palm sago liquid waste, TSS, COD